Information System for Reporting the Provision, Procurement, and Distribution of Production Facilities at the Aceh Animal Health and Livestock Department - Haikal, Andi; Ihsanudin; Suswati, Dewi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Data management related to the provision, procurement, and distribution of production facilities at the Aceh Animal Health and Livestock Department currently relies on manual methods using Microsoft Excel, without utilizing an integrated database system. This study focuses on developing an information system specifically for reporting the provision, procurement, and distribution of production facilities within the department. The objective is to understand and design an Information System for Reporting the Provision, Procurement, and Distribution of Production Facilities using Microsoft Visual Basic.NET. Data collection methods include observation, interviews, and literature review. In this system development, Microsoft Visual Basic.NET is utilized for designing the user interface, while Microsoft Office Access serves as the Database Management System (DBMS). Testing results indicate that the developed system meets the established requirements. The data input process and generated reports align with the desired needs